Profil Pasien DM Tipe 2 dengan Neuropati Pengguna OAD di RSUD Bandung Kiwari - 10060321003, Dela Kurniasih; Umi Yuniarni; Bambang Tri Laksono (Bandung Conference Series: Pharmacy, 2025)
Abstract. Diabetes mellitus (DM) is a chronic metabolic disease that can cause various complications, one of which is diabetic neuropathy. This complication is common in patients with type 2 DM and requires long-term treatment, including the use of oral antidiabetic drugs (OAD). This study aims to determine the profile of patients with type 2 diabetes mellitus with neuropathy complications who use OAD at Bandung Kiwari Regional Hospital. This is an observational study conducted at Bandung Kiwari Regional Hospital from February to May 2025. Data were obtained through demographic data and review of patient medical records. The results obtained stated that the majority of respondents were female (78.95%), aged 56–65 years (39.47%), had an elementary school/Islamic elementary school education (36.84%), worked as housewives (60%), and had suffered from DM for 1–5 years (47.37%). Absrtrak. Diabetes melitus (DM) merupakan penyakit metabolik kronis yang dapat menyebabkan berbagai komplikasi, salah satunya adalah neuropati diabetik. Komplikasi ini umum terjadi pada pasien DM tipe 2 dan memerlukan penanganan jangka panjang, termasuk penggunaan obat antidiabetes oral (OAD). Penelitian ini bertujuan untuk mengetahui profil pasien diabetes melitus tipe 2 dengan komplikasi neuropati yang menggunakan OAD di RSUD Bandung Kiwari. Penelitian ini merupakan studi observasional yang dilakukan di RSUD Bandung Kiwari pada Februari hingga Mei 2025. Data diperoleh melalui data demografi dan telaah rekam medis pasien. Hasil penelitian yang diperoleh menyatakan bahwa mayoritas responden berjenis kelamin perempuan (78,95%), berusia 56–65 tahun (39,47%), berpendidikan SD/MI (36,84%), bekerja sebagai ibu rumah tangga (60%), dan telah menderita DM selama 1–5 tahun (47,37%).